Effect of heat input on the mechanical and metallurgical characteristics of TIG welded joints / subhas Chandra Moi...[et al.] - Subhas, Chandra Moi; Pradip, Kumar Pal; Asish, Bandyopadhyay; Ramesh, Rudrapati (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
This paper presents the study of effect of heat input on the joint quality of tungsten inert gas (TIG) welded specimens. Three different heat input combinations selected as low heat (0.75kJ/mm), medium heat (0.90kJ/mm) and high heat (1.05kJ/mm) have been applied during the operation of TIG welding process on 316L austenitic stainless steel. Welded joints being prepared using a semiautomatic TIG welding machine, the effect of heat input is investigated on the weld bead geometry and mechanical-metallurgical characteristics of the joints. It is observed that as heat input increases, the width of weld bead increases, where as height of weld bead decreases with increasing heat input. Tensile strength as well as hardness increases with increase of heat input up to a threshold value and thereafter it start decreasing. The results of the investigation indicate that the joint prepared using medium heat input depicts higher tensile strength, percentage elongation, yield strength and higher micro hardness value than those joints made using low and high heat input due to smaller dendrite size and lesser interdendritic spacing in the weld zone and formation of very fine skeletal δ-ferrite in plain austenitic matrix. A large number of very fine and shallow dimples are observed in SEM fractograph of the joint made using medium heat input.